PENGEMBANGAN JEJARING SOSIAL BERBASIS WEB SEBAGAI UPAYA PEMBERDAYAAN PEREMPUAN DALAM KEGIATAN PRODUKTIF - , RATRI ABDATUSH S; , Mardhani Riasetiawan, S.E., Ak., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The hight population of women in Indonesia raises concerns in various fields. Existing problems triggered women's empowerment. Empowerment of women is manifested in a variety of activities. On the other hand, the number of women who use social networking is quite high. Social networking can be used for women's empowerment activities. The use of social networks allows many women in different places cooperate in efforts to empower women. These activities require a lot of resources. Meeting the needs od womenâs empowerment resource can use crowdsourcing methods, a method that uses a lot of human resources to complete a job. Development of web-based social networks for womenâs empowerment in productive activities is a women's social network in Indonesia with the main function handles the coordination of joint activities. Social networking is built using PHP programming language, the framework Laravel, MySQL database and twitter bootstrap for the user interface. It provides social networking services such as management of activities, announcements and comments management, logging management, resource management, product management, member management and notification management of activities. This social networking allows women to work together in a productive activity in an effort to empower women.